Optimal Suture Bite Size for Closure of Feline Linea Alba—A Cadaveric Study - Bartier, Amanda L.; Atilla, Aylin; Archer, Rebecca; Kwong, Grace P. S. (Frontiers in Veterinary Science, 2019)
Abstract Objective: This study aimed to determine the most appropriate suture bite and stitch interval (SBSI) size for closing feline linea alba. Study Design: Randomized ex vivo mechanical testing Sample population: Ventral abdominal walls from 35 male feline cadavers were harvested and separated into 125 segments. Methods: Segments were incised along midline then sutured back together using 3-0 polydioxanone using one of the following SBSI: 3, 5, 7.5 or 10mm whereby the distance represents the distance both between the suture bites, and from the bite to incision line. The location of segments as well as the weight of the cadaver were recorded. A single linear distraction mechanical breaking test was performed. Statistical analyses (logistic and linear regression) were performed to determine which factors were associated with visual and mechanical failure, as well as load at failure or maximum displacement. Results: SBSI was significantly associated with load at failure or maximum displacement (p<0.001). In particular, 5mm SBSI had the highest load at failure amongst all the bite sizes (LSmeans=27.55N, 95% Confidence Interval(CI): 23.65–31.44); this was significantly higher than 7.5mm (LSmeans=19.15N, 95% CI: 15.26–23.05, p=0.016) and 10mm (LSmeans=16.55N, 95%CI:12.39–20.70, p=0.0012) but not significantly higher than 3 mm (LSmeans=23.78N, 95% CI: 19.69 – 27.86 p= 0.2). Increased SBSI increased the odds of visual failure (p<0.001) whereas increased weight of the cadaver reduced the odds of visual failure (OR=0.52, 95%CI: 0.30–0.88, p=0.016). Conclusion: The 5 mm SBSI had the highest load at failure and was not significantly different from the 3 mm SBSI when apposing feline linea alba using 3-0 polydioxanone. Clinical significance: Using 5 mm SBSI is the prefered bite size compared to 7.5 or 10 mm SBSI when apposing feline linea alba with 3-0 polydioxanone.